THE EVOLUTION AND DEVELOPMENT OF COMPUTERS - Mirzatullayeva Sayyora Muxammadjonovna (Ustozlar uchun, 2025)
Abstract:. This paper investigates the core role of AI in reshaping computational methods, automating tasks, enhancing decision-making, and facilitating breakthroughs in subfields such as machine learning, robotics, and data analytics. The study further discusses ethical concerns, algorithmic bias, and the future trajectory of AI technologies in the digital age.